Respuesta :

Answer:

Step-by-step explanation:

The steps required to solve the given equation is required.

First step: Identify a = 1, b = 3 and c = -4

Second step: [tex]x=\dfrac{-3\pm \sqrt{3^2-4\times 1\left(-4\right)}}{2\times1}[/tex]

Last step: x = 1 and x = -4

Quadratic equation

The given equation is

[tex]x^2+3x-4=0[/tex]

Comparing with the general quadratic equation [tex]ax^2+bx+c=0[/tex] we have

a = 1

b = 3

c = -4

Applying the formula

[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}\\\Rightarrow x=\dfrac{-3\pm \sqrt{3^2-4\times 1\left(-4\right)}}{2\times1}\\\Rightarrow x=1\ \text{and}\ -4[/tex]

Learn more about solving quadratic equations:

https://brainly.com/question/1214333